Blurring bioart boundaries - Pietarinen, Heidi; Qureshi, Amna (Frontiers in Communication, 2024)
This study investigates the intersection of bioart and posthumanistic perspectives through the innovative use of reindeer by-products, specifically reindeer blood, as a medium for artistic expression. Utilising an Arts-Based Research (ABR) approach, the research investigates the methodological, ethical, and cultural dimensions of integrating waste materials into creative practices. The project repurposes reindeer blood, an often-overlooked by-product of reindeer herding, to provoke ethical discussions on sustainability and cultural sensitivity within the arts. Experiments in the BioARTech laboratory transform reindeer blood into air-dried pigment, which is then incorporated into glassblowing and surface pattern design. These innovative techniques challenge traditional boundaries of artistic materials and prompt deeper reflections on human-nature relationships. Exhibitions across Finland highlight the ethical application of this unique Northern material, highlighting its cultural significance and promoting a reimagining of our interconnectedness with the natural world. Ultimately the study expands the artistic repertoire and advocates for more harmonious and sustainable futures through pioneering bioart practices.